2021
DOI: 10.1002/cpa.21990
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Transport Based Seismic Inversion:Beyond Cycle Skipping

Abstract: Full‐waveform inversion (FWI) is today a standard process for the inverse problem of seismic imaging. PDE‐constrained optimization is used to determine unknown parameters in a wave equation that represent geophysical properties. The objective function measures the misfit between the observed data and the calculated synthetic data, and it has traditionally been the least‐squares norm. In a sequence of papers, we introduced the Wasserstein metric from optimal transport as an alternative misfit function for mitig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 77 publications
(106 reference statements)
1
23
0
Order By: Relevance
“…Note that wavefields are not naturally probability distributions. Thus, when we implement the W 2 natural gradient, we normalize the data to be probability densities following [10,11]. As we have discussed in Remark 2.3, the W 2 and Ḣ−1 natural gradients are closely related, which are also reflected in this numerical example as the reconstructions in Figure 5e and Figure 5f are very similar.…”
Section: Full Waveform Inversionsupporting
confidence: 60%
See 1 more Smart Citation
“…Note that wavefields are not naturally probability distributions. Thus, when we implement the W 2 natural gradient, we normalize the data to be probability densities following [10,11]. As we have discussed in Remark 2.3, the W 2 and Ḣ−1 natural gradients are closely related, which are also reflected in this numerical example as the reconstructions in Figure 5e and Figure 5f are very similar.…”
Section: Full Waveform Inversionsupporting
confidence: 60%
“…We avoid dealing with the nonconvexity by choosing a good initial guess as shown in Figure 5b. One may also choose other objective functions such as the Wasserstein metric to improve the optimization landscape [11]. We follow Subsection 3.3 to carry out the implementation for various natural gradient descent methods since the Jacobian ∂ θ ρ is not explicitly given, and the adjoint-state method has to be applied based on (4.1).…”
Section: Full Waveform Inversionmentioning
confidence: 99%
“…Full waveform inversion (FWI) has been receiving wide attention in recent years [9,14,22,32,36,37] due to its high-resolution imaging in geophysical properties. Generally, it can be formulated as a PDE constrained optimization problem in mathematics, which consists of two parts [31]: the forward modeling of seismic wavefield, and the optimization problem searching for suitable model parameters to minimize the mismatch between the predicted and observed seismic signals.…”
Section: Introductionmentioning
confidence: 99%
“…A more convex misfit function also implies a more robust solution to the inverse problem when subject to uncertainties in the input parameters. Rigorous mathematical treatment [13] has in fact shown that 1-D quadratic Wasserstein distances (a subset of OT distances) are convex functions with respect to dilation and translation when applied to probability density functions. In order for this to remain valid for generic signals as well, it is however necessary to normalize and positivize them accordingly.…”
Section: Introductionmentioning
confidence: 99%